Analysis of Tax Collection with Reprimand and Forced Letters to Optimize Tax Revenue at KPP Pratama Jambi Telanaipura - Fithri Salsabila; Yudi; Wiwik Tiswiyanti (International Journal of Integrative Sciences, 2023)
As a form of law enforcement to improve taxpayer compliance with paying their taxes, tax collection is carried out consistently and continuously. The tax collection activities carried out by the Fiscus consist of active tax collection and collection by forced letter. Active billing is carried out by the Fiscus by issuing tax assessment letters, reprimand letters, and tax bills. If the taxpayer does not also pay his tax debt, the tax officer can take tax collection action with a forced letter. This study aims to analyze the implementation of tax collection with reprimand letters and forced letters to optimize tax revenue at KPP Pratama Jambi Telanaipura in 2020 and 2021. The research method used is a qualitative descriptive analysis method. The data collection method used was interviews and documentation at KPP Pratama Jambi Telanaipura. Based on the results of the analysis, it shows that tax collection with reprimand letters and forced letters are classified as ineffective. Tax collection with reprimand letters and forced letters at KPP Pratama Jambi Telanaipura greatly does not contribute to tax revenue. KPP Pratama Jambi Telanaipura's efforts in optimizing tax revenue include holding focus group discussions, joining collection programs, canvassing, and providing tax education, socialization, and counseling